Solitary squamous papilloma of the bronchus. - Maxwell, R J (1985)
A case of solitary squamous papilloma of the bronchus is described and 11 other cases from the reports published worldwide are reviewed. These tumours present in middle aged men with symptoms similar to those of bronchial carcinoma. Treatment by bronchoscopic removal or lobectomy is usually curative. Symptoms are similar to those of bronchial carcinoma, but a correct preoperative diagnosis permits more conservative surgery to be carried out. Difficulties in the histological classification of papillary tumours of the bronchus are discussed.